Pitfalls and potential of high-throughput plant phenotyping platforms - Poorter, Hendrik; Hummel, Grégoire M.; Nagel, Kerstin A.; Fiorani, Fabio; von Gillhaussen, Philipp; Virnich, Olivia; Schurr, Ulrich; Postma, Johannes A.; van de Zedde, Rick; Wiese-Klinkenberg, Anika (Frontiers in Plant Science, 2023)
Automated high-throughput plant phenotyping (HTPP) enables non-invasive, fast and standardized evaluations of a large number of plants for size, development, and certain physiological variables. Consequently, many universities andMany research institutesgroups recognize the potential of HTPP and have made significant investments in HTPP infrastructure, or are considering to dodoing so. To make optimal use of scarcelimited resources, it is important to plan and use these facilities prudently and to interpret the results carefully. Here we present a number of points that users should consider before purchasing, building or utilizing such equipment. They relate to (1) the financial and time investment for acquisition, operation, and maintenance, (2) the constraints that comeassociated with such machines in terms of flexibility and growth conditions, (3) the pros and cons of frequent non-destructive measurements, (4) the level of information level provided by proxy traits, and (5) the useutilization of calibration curves. We concludeUsing data from an Arabidopsis experiment, we demonstrate how diurnal changes in leaf angle can impact plant size estimates from top-view cameras, causing deviations of over 20%. Growth analysis data from another rosette species showed that there was a curvilinear relationship between total and projected leaf area. Neglecting this curvilinearity resulted in linear calibration curves that, although having a high r 2 (> 0.92), also exhibited large relative errors. Another important consideration we discussed is the frequency at which calibration curves need to be generated and whether different treatments, seasons, or genotypes require distinct calibration curves. In conclusion, HTPP systems have become a valuable addition to the plant biologist's toolbox of plant biologists, provided that these systems are tailored to the research questions of interest, and users are aware of both the possible pitfalls and potential involved.